The work of nations preparing ourselves for 21st-century capitalism - Reich, Robert B. 1946- (Knopf, 1991)
An analysis of what nations must do if their citizens are to flourish in the twenty-first century.
Keywords: Capitalisme; Economisch nationalisme; Investissements publics; Kapitalisme; Libre entreprise; Politique économique; Wirtschaftsentwicklung; Wirtschaftstheorie; Kapitalismus; Wirtschaftspolitik; Capitalism; Free enterprise; Public investments; Economic policy; Weltwirtschaft; Wirtschaftliche Integration; Unternehmen; Strukturwandel; Nationalbewusstsein; Internationale Wettbewerbsfähigkeit; USA